Respons Siswa terhadap Masalah Komunikasi dalam Kelas EFL Tingkat Sekolah: Kajian Pustaka Naratif - Putri, Shofa salsabilla; Kelik Wachyudi; Hilmansyah Saefullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Communication problems often occur in school-level English as a Foreign Language (EFL) classrooms. Students may experience difficulties when speaking, answering teachers’ questions, participating in discussions, delivering short presentations, or interacting with peers in English. These difficulties are not only related to vocabulary, grammar, and pronunciation, but also influenced by speaking anxiety, self-confidence, classroom atmosphere, peer support, and the teacher’s role. This article aims to synthesize previous research findings on students’ responses to communication problems in school-level EFL classrooms. Using a narrative literature review approach, this article examines theoretical books and research articles relevant to communication strategies, speaking anxiety, willingness to communicate, and oral communication barriers in EFL contexts. The synthesis shows that students’ responses can be understood through four main patterns: responses to maintain communication, avoidance responses, responses influenced by anxiety, and responses shaped by classroom support. This review argues that silence, long pauses, first-language use, and short answers do not necessarily indicate students’ inability. These responses may reflect language barriers, affective pressure, limited strategic competence, or the need for a more supportive speaking environment. The findings imply the importance of speaking instruction that is safe, gradual, communicative, and able to provide students with explicit opportunities to develop and use communication strategies consciously.